Administration, Governance And Management In Education: A Case Study Of Uzbekistan (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
This article examines the reform of educational administration, governance and management in Uzbekistan between 2017 and 2025. It distinguishes administration as the formal regulatory structure, management as the operational leadership of institutions and governance as the distribution of authority and accountability among stakeholders. The study shows that Uzbekistan has substantially modernised its educational governance architecture through ministerial reorganisation, the Law on Education, higher-education autonomy, quality assurance reforms and digital management systems. However, the article also argues that structural change has moved faster than management culture. The main unfinished tasks are the professional development of school and university leaders, the practical implementation of institutional autonomy, stronger stakeholder participation and the transition from compliance-based control to evidence-informed professional judgment
Keywords: educational governance; management; administration